Migration, family and networks: Timorese seasonal workers' social support in Australia. (27th May 2021) - Wu, Annie Yuan Cih
Abstract : This paper explores the social support of Timorese workers under the Australian Seasonal Workers Programme (SWP). The SWP, which allows citizens from Pacific Island countries and Timor‐Leste to work in Australian agriculture for six to nine months, has become the major source of remittances for seasonal workers from Timor‐Leste. The paper describes how access to the internet and the availability of social media devices can help to maintain long‐distance family relationships, support migrants' well‐being and alleviate the effects of socio‐spatial segregation to some extent. However, the need to earn remittances in a fixed period of time forces them to accept a trade‐off in the quality of their social and personal lives in rural Australia. According to the New Economics of Labour Migration (NELM), isolation and separation from families are part of a rational household strategy to accumulate remittances. This paper argues that insufficient attention has been paid to the social costs borne by workers and left‐behind households and that the sustainability of the SWP depends to a large extent on the ability of workers to find ways of meeting their needs for social support. The analysis is based on data from participant observation and semi‐structured interviews with 50 Timorese seasonal workers in Australia and Timor‐Leste.